The Influence of Cooperation with Business Partners, Agricultural Technology Implementation, and Religiosity on the Welfare of Al-Mahdi Farmers in Percut Sei Tuan District - Rokan, Mustapa Khamal; Harahap, Muhammad Ikhsan; Sihotang, Indah Khairunnisa (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2025)
This study aims to analyze the influence of business partnerships, agricultural technology adoption, and religiosity on farmers' welfare. The research was conducted among members of the Al-Mahdi Farmer Group in Percut Sei Tuan District using a quantitative approach. Data were collected through questionnaires distributed to 52 respondents and analyzed using multiple linear regression. The results show that jointly, the three independent variables have a significant effect on farmers' welfare. Partially, the adoption of agricultural technology and religiosity have a positive and significant influence, while business partnerships do not have a significant impact. These findings indicate that improving farmers' welfare is not solely determined by technical aspects or economic cooperation, but is also strongly influenced by spiritual values and local cultural norms within farming communities. This study implies that sustainable agricultural development must integrate both technological and spiritual approaches to support holistic farmer well-being.